Knowledge of Postgraduate Research Scholars of Anand Agricultural University about GlobalWarming - J.B.Dobariya, N.B.Chauhan, (Indian Journal of Extension Education, 2022)
Global warming has an impact on our planet, agriculture, human and animal lives. The future problems caused by globalwarming are raising sea water, growing deserts and more frequent droughts, all looks set to affect the developing worldmore than rich countries. In an effort to combat against global warming, issues related to agricultural development,agricultural research scholars as a future generation of agricultural development need to possess general awareness andknowledge about global warming issues and problems. Focused and timely efforts to apply knowledge by the agriculturalresearch scholars can enable them to stand successfully against the global warming problems to play a leadership role inoverall development of agriculture. The present study was undertaken on a random sample of 100 postgraduate researchscholars studying in agriculture faculties of B. A. College ofAgriculture,AnandAgricultural University located atAnandof Gujarat state. Selected dependent and independent variables were measured with the help of suitable scale andprocedures. The level of knowledge of the postgraduate scholarswas observed significantly higher among those who hadhigher academic performance, involvement in extracurricular activity, information collection habit, more than oneoccupation of family, elevated scientific orientation and positive attitudes towards integrated pestmanagement.